(untitled) (Nigerian Journal of Technology, 2021)
This study involves understanding the effect of tricycles on saturation flow rate at signalized intersections. The goal is to show that intersection dominated by tricycle experience congestion especially at peak periods (morning and evening). This was done by collecting vehicular traffic data, signal timing and geometric data from five (5) signalized intersections at ten (10) cycles. The period covered October, 2015 to June, 2016 for four working days of the week (Mondays, Tuesdays, Wednesdays, and Fridays), between the hours of 7:30 am–9:30 am and 4:30 pm–6:30 pm. The duration of data collected covered both rainy and dry seasons. Average vehicular departure time during green time was determined and saturation flow obtained through field measurement by the ratio of average vehicular departure time to green time. Highway Capacity Manual method was also used to obtain saturation flow at each study approach. Saturation flow obtained through field measurement and Highway Capacity Manual were compared using independent t-test having t-value of 4.239 and P-value of 0.000 at 20 degree of freedom were obtained. The analysis indicated that P-value is less than 0.05, hence the mean of Highway Capacity Manual 2000 Model (5918.60) was significantly higher than the field measurement (4687.50). The result indicated that the increasing rate of tricycle with non-lane discipline causes congestion at signalized intersection. The findings suggest that the widely used Highway Capacity Manual is not appropriate for determining saturation flow for a mixed traffic with increasing rate of tricycle coupled with non-lane discipline traffic condition. From the analysis, it is recommended that Government should give priority to use of buses as a means of mass transit system so that it can accommodate more commuters than tricycle. http://dx.doi.org/10.4314/njt.v40i2.4